URANIUM AND THORIUM UPAKE BY LIVE AND DEAD CELLS OF BACILLUS SP - SUJIN JEBA KUMAR.T.; BALAVIGNESWARAN.C.K (International Journal of Pharma and Bio Sciences, 2012)
Bacillus Sp. was isolated near the mining area and was studied for biosorption U and Th. This study presents uptake of uranium (U) and thorium (Th) by live and dead cells of Bacillus Sp. Increasing concentration of U and Th showed decrease in absorption by Bacillus Sp. Dead cells of Bacillus Sp. exhibited same or more uptake of U and Th than living cells. Increasing temperature promotes uptake of U and Th by Bacillus Sp.